What lies beneath—Negative interest rates and bank lending - Schelling, Tan; Towbin, Pascal (Journal of Financial Intermediation, 2022)
We study the transmission of negative interest rates to bank lending around an unexpected policy rate cut into deep negative territory by the Swiss National Bank (−0.75%). We exploit a rich data set on transaction-level corporate loans matched with bank balance sheet data. We find that banks more affected by negative interest rates offer looser lending terms and lend more than other banks. This result is consistent with the risk-taking channel, where a lower policy rate spurs bank risk-taking to maintain profits. The result implies that, even in such deep negative territory, the reversal rate has not yet been hit.